2017
DOI: 10.1016/j.eurpsy.2017.01.602
|View full text |Cite
|
Sign up to set email alerts
|

Impact of coping strategies on emotional status in patients with obstructive sleep apnea syndrome

Abstract: IntroductionObstructive sleep apnea syndrome (OSAS) is a common sleep disorder, which leads to higher morbidity, and mortality and can result in various psychological problems, such as depression.ObjectivesThe purpose of this study was to assess the severity of depression and to examine its relationships with coping strategies in OSAS patients.MethodsWe performed an analytical cross-sectional study of 87 recently diagnosed OSAS patients. Apnea hypopnea index (AHI) was determined by an overnight polysomnography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 0 publications
0
8
3
Order By: Relevance
“…In contrast, Bardwell et al (2001) concluded that the more active and less passive the coping strategies reported by OSA patients are, the lower the level of depressive symptoms they experienced. Depressive symptoms were associated with more emotional coping and with less problem-focussed coping in the study by Gassara et al (2017). Although our results differ from those of previous studies (Bardwell et al, 2001; Gassara et al, 2017), these discrepancies may be associated with the difference in OSA diagnosis criteria; for example, patients in the study by Bardwell et al (2001) were diagnosed using a Respiratory Disturbance Index of ⩾15, while in our study, OSA diagnosis was stated based on an AHI of ⩾5.…”
Section: Discussioncontrasting
confidence: 95%
See 4 more Smart Citations
“…In contrast, Bardwell et al (2001) concluded that the more active and less passive the coping strategies reported by OSA patients are, the lower the level of depressive symptoms they experienced. Depressive symptoms were associated with more emotional coping and with less problem-focussed coping in the study by Gassara et al (2017). Although our results differ from those of previous studies (Bardwell et al, 2001; Gassara et al, 2017), these discrepancies may be associated with the difference in OSA diagnosis criteria; for example, patients in the study by Bardwell et al (2001) were diagnosed using a Respiratory Disturbance Index of ⩾15, while in our study, OSA diagnosis was stated based on an AHI of ⩾5.…”
Section: Discussioncontrasting
confidence: 95%
“…A second model included a clinical variable (OSA severity – measured by AHI), and a third model included night-time sleep quality and daytime sleepiness. In the fourth and fifth model, hostility and all dimensions of CSE were included separately (following Bardwell et al, 2001; Gassara et al, 2017; Mikula et al, 2019) to assess the explained amount of the total variance of psychological distress.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations